The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jcmm.15054
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs: How to regulate the metastasis of non–small‐cell lung cancer

Abstract: Non–small‐cell lung cancer (NSCLC) has become the most lethal human cancer because of the high rate of metastasis. Hence, clarifying the molecular mechanism underlying NSCLC metastasis is very important to improve the prognosis of patients with NSCLC. Long non‐coding RNAs (LncRNAs) are a class of RNA molecules longer than 200 nucleotides, which can participate in diverse biological processes. About 18% of human LncRNAs were recently found to be associated with tumours. Many studies indicated that aberrant expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 114 publications
0
28
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) were once considered as "noise" in genomes, however, their functions in a variety of cancers, including NSCLC, are recently appreciated (9)(10)(11)(12)(13)(14). It was reported that actin filament-associated protein 1 antisense RNA 1 (AFAP1-AS1) aggravates tumorigenesis and drug resistance in NSCLC (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) were once considered as "noise" in genomes, however, their functions in a variety of cancers, including NSCLC, are recently appreciated (9)(10)(11)(12)(13)(14). It was reported that actin filament-associated protein 1 antisense RNA 1 (AFAP1-AS1) aggravates tumorigenesis and drug resistance in NSCLC (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…A major mechanism by which lncRNAs regulate EMT is by epigenetically silencing EMT-related genes such as E-cadherin via recruitment of transcriptional repressors like PRC2 (Lin et al, 2018). Alternatively, lncRNAs contribute to the modulation of EMT by acting as competing endogenous RNAs (ceRNAs) for EMT-associated miRNAs and impeding the interaction of these miRNAs with their target molecules in a stoichiometric manner Fang et al, 2020). In terms of the canonical miR-200/ZEB double negative feedback loops which are critical to the induction of EMT, a number of lncRNA including lncRNA-ATB, H19 and HULC upregulate ZEB1/2 by competitively binding the miR-200 family and induce EMT (Yuan et al, 2014;Liang et al, 2015;Expósito-Villén et al, 2018;Ashrafizadeh et al, 2020).…”
Section: Lncrnamentioning
confidence: 99%
“…Patients with NSCLC accounted for nearly 85% of all patients with lung cancer, and the most prevalent pathological pattern of NSCLC was lung adenocarcinoma (LUAD) [ 2 ]. In recent decades, many researchers have concentrated on studying the potential biological and molecular mechanisms of lung cancer, and the molecular mechanisms are gradually being understood [ 3 ]. It was recognized that identifying key molecular abnormalities would promote the rapid development of precision medicine, and more effective strategies will be identified for the diagnosis, treatment and prognosis of LUAD in the near future [ 4 ].…”
Section: Introductionmentioning
confidence: 99%